Filial piety expectations and loneliness among older people in Kuantan, Pahang - Makhtar, Aniawanis; Samsudin, Nor Hafizah (Makara Journal of Health Research, 2020)
Background: Filial piety plays a vital role in combating loneliness among older people. Older adults have a high tendency to feel lonely when affection toward and from their children decreases. This study aimed to determine the association between filial piety expectations and loneliness among older people in Kuantan, Pahang. Methods: A cross-sectional study was conducted on 198 older people in Kuantan, Pahang. Filial piety expectation and loneliness were measured by the Filial Piety Expectation Scale and UCLA (University of California, Los Angeles) Loneliness Scale questionnaire. The data were analyzed by using SPSS version 22.0. Results: The results of this study indicate that the majority of respondents believe that adult children should care for their parents. A high level of filial piety expectations was associated with a low level of loneliness. Age and race were significantly associated with filial piety expectations among older people in Kuantan. Conclusion: The study showed an association between filial piety expectations and loneliness among older people. Thus, the influence of filial piety expectations on the level of loneliness among older people must be acknowledged to ensure the improvement of the health and well-being of older people.